Bicalutamide and the new perspectives for female pattern hair loss treatment: What dermatologists should know - Carvalho, Raquel de Melo; Santos, Leopoldo Duailibe Nogueira; Ramos, Paulo Müller [UNESP]; Machado, Carla Jorge; Acioly, Patricia; Frattini, Simone Carolina; Barcaui, Carlos Baptista; Donda, André Luiz Vairo; Melo, Daniel Fernandes (Wiley, 2022)
Female pattern hair loss (FPHL) is the most common form of alopecia in women. FPHL may compromise body image and strongly affect self-esteem, negatively impacting quality of life. Currently, the only Food and Drug Administration (FDA) approved drug for its treatment is topical minoxidil, with a variable response rate. Recently, a few studies in FPHL have pointed out bicalutamide as an emergent selective androgen receptor antagonist with a favorable safety and tolerability profile. This review aimed to summarize and discuss the key information on this new therapy for FPHL. Bicalutamide has no diuretic effect. It does not cross the blood–brain barrier, and it has little effect on serum luteinizing hormone. Additionally, bicalutamide was found to be effective on women presenting with other features of hyperandrogenism such as seborrhea, acne, and hirsutism with mild and well-tolerated adverse effects. Despite the high prevalence and psychosocial impairment, FPHL treatment remains challenging. Therefore, although future prospective, comparative, randomized clinical trials are essential to establish the ideal dose and efficacy of the drug, oral bicalutamide appears to be a promising option to expand the arsenal of FPHL treatment.
Keywords: alopecia; androgenetic alopecia; antiandrogens; bicalutamide; female pattern hair loss